2016
DOI: 10.1021/acs.chemmater.6b03555
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Structure–Composition–Property Relationships of the β-SiAlON:Eu2+ Phosphor

Abstract: In this work, we performed a systematic investigation of structure−composition−property relationships in Eu 2+ activated β-SiAlON, one of the most promising narrow-band green phosphors for high-power light-emitting diodes and liquid crystal display backlighting with wide color gamut. Using first-principles calculations, we identified and confirmed various chemical rules for Si−Al, O−N, and Eu activator ordering within the β-SiAlON structure. Through the construction of energetically favorable models based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
72
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 33 publications
16
72
5
Order By: Relevance
“…The obtained reliability factors Rwp, Rp, and x 2 all imply a good fitting quality and no secondary phase was detected. Meanwhile, the refined NPD data also indicate that O shows an overwhelmingly preferential occupation of the N2 (2c sites), in line with the result of the literature 14 . This occurrence provides abundant microenvironment around Eu 2+ with different ratios of O/N in the second coordination zone ( Figure S3).…”
Section: Leds Fabrication and Performance Measurementsupporting
confidence: 89%
See 2 more Smart Citations
“…The obtained reliability factors Rwp, Rp, and x 2 all imply a good fitting quality and no secondary phase was detected. Meanwhile, the refined NPD data also indicate that O shows an overwhelmingly preferential occupation of the N2 (2c sites), in line with the result of the literature 14 . This occurrence provides abundant microenvironment around Eu 2+ with different ratios of O/N in the second coordination zone ( Figure S3).…”
Section: Leds Fabrication and Performance Measurementsupporting
confidence: 89%
“…To date, in β-SiAlON:Eu, the consensus is that a single crystallographic site existed in the highly symmetric hexagonal channel for the Eu 2+ dopant, coordinated by nine (N,O) atoms. [14][15][16] However, it was still absent of direct evidences to prove the precise microenvironment of Eu 2+ in β-SiAlON. This fundamental question enables us to consider using the exhaustive photoluminescence measurements, such as high pressure and time-resolved spectroscopy, as an option to probe it.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…1a tells that the densely packed, corner-sharing (Si,Al)(N,O) 4 tetrahedra form a three-dimensional network with a one-dimensional channel running along the c-axis. 22,23 Density functional theory (DFT) calculations based on the Vienna ab initio Simulation Package (VASP) are used to generate the potential energy surface, as illustrated in Fig. 1b.…”
Section: β-Sialon:eumentioning
confidence: 99%
“…Wang 23 et al demonstrated that z value (Si/Al ratios or oxygen concentrations) could have a significant effect on the local environment of Eu 2+ in β-SiAlON. As shown in Fig.…”
Section: β-Sialon:eumentioning
confidence: 99%